Pengelolaan Anggaran Dana Bantuan Operasional Sekolah Pada Masa Pandemi Di SMPN 15 Palangka Raya - Tonich Uda; Dea Natalia Banjarnahor; Rinto Alexandro; Fendy Hariatama (FKIP Universitas Palangka Raya, 2022)
School Operational Assistance Fund (BOS) is a government program in the form of financial assistance that aims to provide non personnel funding for basic education units and secondary school as the implementation of compulsory education, the Regular BOS Fund is allocated to assist the operational expenditure needs of all students in primary and secondary education units. Method research is a qualitative descriptive study. The research subjects included the school principal, treasurer and school committee. The data analysis technique used qualitative data analysis. The results showed that the management of the BOS Fund at SMP Negeri 15 Palangka Raya during the pandemi was managed properly in accordance with the Technical Guidelines for the use of the 2021 BOS Fund, the Covid-19 pandemi had an impact on the management of the use of the BOS Fund, where the BOS Fund was usedrelated to efforts to prevent the transmission of Covid-19, at SMP Negeri 15 Palangka Raya the BOS funds are used by schools to complete facilities and infrastructure to support learning activities during the pandemi, where SMP Negeri 15 Palangka Raya applies semi-online learning and also BOS funds are used to prepare supporting facilities and infrastructure Limited Face-to-face Learning.